Penentu Kualitas Audit: Audit Capacity Stress, Kompetensi, Pengalaman Audit, atau Skeptisme Profesional? - Maulida, Lida Laila; Ahdi, Makmuri; Widagdo, Ridwan (AKTSAR: Jurnal Akuntansi Syariah, 2026)
This study aims to analyze the effect of Audit Capacity Stress, Competence, Audit Experience, and Professional Skepticism on Audit Quality at Public Accounting Firms in South Jakarta. The population in this study consists of all auditors from Public Accounting Firms in South Jakarta who are registered with the Financial Services Authority and actively conduct audits of public and private companies. The research sample was taken using purposive sampling. The testing was conducted using descriptive statistical tests, classical assumption tests, and hypothesis tests. The results of the study show that audit capacity stress, competence, and audit experience do not significantly affect audit quality. Meanwhile, professional skepticism has a significant effect on audit quality.